Barriers to cycling, barriers to health equity: Disparities in perceived cycling environments in the U.S. - Lindsay M. Braun (Journal of Cycling and Micromobility Research)
Marginalized groups often face disproportionate environmental barriers to cycling, which could contribute to sociodemographic disparities in safety and health. Studies of these barriers typically rely on objective measures of infrastructure access, which are useful but may not capture important factors such as infrastructure quality and traffic safety. I address this gap by examining perceived barriers to cycling in a nationally representative sample of U.S. adults (n = 222,344) drawn from the 2017 National Household Travel Survey, asking three research questions through an equity lens: (1) Who cycles? (2) Which types of cyclists report environmental barriers? (3) Do these barriers moderate the potential health benefits of cycling? Using Heckman selection and multinomial logistic regression models, I find that marginalized groups (i.e., people of color and those with low socioeconomic status) are less likely to cycle, and more likely to face infrastructure- and safety-related barriers when they do. I also find that associations between cycling and self-reported health, while generally positive, are weaker among cyclists who report environmental barriers. These results suggest that there are sociodemographic disparities in perceived barriers to cycling in the U.S., and that addressing these disparities should be a critical focus for equitable cycling promotion.